Fins and Fin Rays from Whale Shark (Rhiniodon typus Smith) - A., Ramachandran; T.V., Sankar (Fishery Technology, 2025)
The whale shark (Rhiniodon typus Smith) is an under exploited species and it is mainly caught for its liver oil. The processing of shark fin for rays is reported here. The fins have a high content of rays. The yield of lin rays from undried lins ranged from 0.53 to 4.40 percent with maximum ray content in the lower lobe of caudal fin. The physical and chemical characteristics of the rays are reported. The total nitrogen content is about 15 to 16 percent (dry weight basis).